(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Oo AT, Minh DD. 2025. Assessment of the water insecurity of rice and fish farmers in the coastal areas of Myanmar and Vietnam. Asian J Agric 9: 191-200. Farm households along the coastlines of Myanmar and Vietnam are susceptible to climate-related hazards and the adverse effects of water insecurity. To understand the level of water insecurity of rice and fish farming households, this study examines water insecurity of households by using Guttman’s Water Insecurity Indexing (WII) analysis. This study was conducted with 899 farm households from Myanmar and Vietnam. A total of 29 indicators were selected and constituted into four major components. According to a total aggregate score, rice-farming households are more susceptible to accessing water sources and services than fish-farming households in both countries. Compared to farm households in Myanmar, farm households in Vietnam are particularly vulnerable to access to water sources, with scores of 0.414 and 0.334. There is little variation in the water resource management score. However, Myanmar’s farm households indicated more inadequate adaptation capacity (0.487) than Vietnam’s (0.462). Moreover, an idealized Guttman’s scale indicated that farm households in Myanmar had a lower level of intervention capability and adaptive capacity than farm households in Vietnam. The findings highlight the necessity of improving intervention capability and capacity and accessibility measures to improve the water security of farm households in both Myanmar and Vietnam.